Resistance Response of the Jasmonic Acid and Salicylic Acid Signaling Pathways in Mango Fruits Infected with Lasodiplodia theobromae - QU Xiangxiang, HU Meijiao, SUN Jinhua, GONG Deqiang, GAO Zhaoyin, CHEN Gengxin, LI Min (Shipin Kexue)
In order to explore the response patterns of the jasmonic acid (JA) and salicylic acid (SA) signaling pathways in mango fruits to Lasiodiplodia theobromae, we analyzed the synthesis of JA and SA in L. theobromae mycelia infecting the fruit and in the infected fruit as well as the expression of genes involved in the JA and SA signaling pathways and the expression of resistance-related genes. The results showed that the production of JA and SA in the mycelia gradually increased with increasing infection time. JA production increased significantly in the inoculated fruit, while SA production decreased significantly with increasing storage time (P < 0.05). The expression of genes related to JA signaling pathway, such as jasmonate resistant 1 (MiJAR1), allene oxide synthase (MiAOS), and myelocytomatosis 2 (MiMYC2) were rapidly up-regulated at the early stage and down-regulated at the late stage. The gene expression of coronatin insensitive 1 (MiCOI1) was continuously down-regulated. The gene expression of isochorismate synthase (MiICS), a SA signaling pathway-related gene, was down-regulated, while the gene expression of non-expressor of pathogenesis-related genes 1 (MiNPR1) was up-regulated at the early stage and down-regulated at the late stage. The expression of resistance-related genes, such as phenylalanine ammonia lyase (MiPAL), peroxidase (MiPOD), and β-1,3-glucanase (MiGLU) were up-regulated at the early stage, while the expression of chitinase gene (MiCHI) was continuously up-regulated after 12 h. Overall, these results indicate that infection with L. theobromae activates the synthesis of JA and its signal transduction, but inhibits the synthesis and signal transduction of SA in mango fruits.